Pengaruh Kepuasan Petani Ulat Sutera terhadap Loyalitas sebagai Plasma pada Pola Kemitraan Agrowisata Sutera Sari Segara - LUH TRIASTITI MANIK ADHITA; I KETUT SUAMBA; NI WAYAN PUTU ARTINI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2020)
The Effect of Silkworm Farmer Satisfaction on Loyalty as Plasma on the Silk AgroTourism Pattern of Sutera Sari Segara Agro Tourism Sutera Sari Segara is an agrotourism that presents natural silk activities,ranging from mulberry tree cultivation to weaving silk thread into silk. Mistakes thatgenerally occur in partnership companies are the creation of partnership agreements by oneparty, late delivery of production facilities, and late payments. The purpose of this studywas to determine the partnership pattern between Sutera Sari Segara Silk Agrotourism andpartner farmers and analyze the effect of silkworm farmer satisfaction on loyalty asplasma. Respondents in this study were 40 partner farmers who were obtained based onnon-probability sampling with judgmental sampling. The model is designed based on theStructural Equation Modeling (SEM) approach based on SmartPLS version 3.0. Theresults showed that the partnership pattern between Sutera Sari Segara Silk Agro Tourismand partner farmers was a plasma core pattern. The three service variables have a positiveand significant effect on farmer satisfaction. The service variables of cultivationtechniques have the greatest influence on farmer satisfaction. The variable farmersatisfaction with loyalty has a positive and significant value. Based on the results of thisstudy, it is expected that Sutera Sari Segara Silk Agro Tourism in making partnershipagreements can involve partner farmers. The quality of service provided by the Sari SegaraAgrotourism is good. However, it needs to be improved to maintain and improve farmersatisfaction, so that farmers become loyal.